Southwest Research-Extension Center, Field Day 2009 (Kansas Agricultural Experiment Station Research Reports, 2009)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: SRP1014; 2009; crops; tillage; soil fertility; weed science; insect control; irrigation